Online Base Transportation Service Quality and Customers Satisfaction Analysis - Dengah, Josephine Angela; Indrajit, Indrajit (Faculty of Economics and Business, Universitas Klabat, 2024)
This study investigates how customer satisfaction is influenced by various service quality factors, including price, convenience, safety, and information and communication technologies (ICT). The study focused on Go-Jek users in Airmadidi and its surrounding areas, encompassing both frequent and first-time users. Data were collected using a Google Forms questionnaire from a sample of 315 respondents selected through convenience sampling. Prior to distribution, the validity and reliability of the questionnaire were tested with 37 respondents in a pilot study. Pearson correlation coefficients were calculated to assess the relationships between the different service quality attributes (safety, price, convenience, ICT) and customer satisfaction. The results revealed a strong relationship between customer satisfaction and the service quality factors of safety, price, convenience, and ICT. Among these factors, ICT showed the strongest association with customer satisfaction.